2008
DOI: 10.1523/jneurosci.0224-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Subventricular Zone-Mediated Ependyma Repair in the Adult Mammalian Brain

Abstract: The subventricular zone (SVZ) of the adult mouse brain is a narrow stem cell niche that lies along the length of the lateral wall of the lateral ventricles. The SVZ supports neurogenesis throughout adulthood; however, with increasing age, the ventral SVZ deteriorates and only the dorsolateral SVZ remains neurogenic. Associated with the elderly dorsolateral SVZ, we reported previously an increased number of astrocytes interposed within the adjacent ependymal lining. Here, we show that astrocytes integrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 38 publications
4
133
2
Order By: Relevance
“…Recent evidence demonstrating regenerative repair in the ependymal layer from astrocytes [26] suggests that active signaling processes may be involved in maintaining a viable ependymal layer in health and during pathologic injury. Involvement of purinergic signaling and/or Ca 2+ -mediated second messenger pathways in initiating such repair is one intriguing possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrating regenerative repair in the ependymal layer from astrocytes [26] suggests that active signaling processes may be involved in maintaining a viable ependymal layer in health and during pathologic injury. Involvement of purinergic signaling and/or Ca 2+ -mediated second messenger pathways in initiating such repair is one intriguing possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of these astrocytes between P19 and P21 is dependent on FoxJ1 expression as their density is severely depleted in the FoxJ1 -/-SVZ. Recent studies have described the expansion of a unique set of astrocytes in the aged ependymal layer (Luo et al, 2006), a phenomenon later shown to be involved in the repair of ependymal cells in elderly mice (Luo et al, 2008). It is possible that the small population of resident FoxJ1 + astrocytes might participate in the repair of the aged ependymal layer.…”
Section: Foxj1mentioning
confidence: 99%
“…First, with reports documenting the importance of ependyma-derived factors such as regulators of bone morphogenetic proteins signaling, pigment epithelium-derived growth factor, and stromal cell-derived factor 1 in the control of NSC activity [23][24][25]. Second, with the evidence that adult NSCs can respond to ependymal cell loss by replacing the damaged cells [26]. They also corroborate observations in the early postnatal brain, when the maturation of adult NSCs follows the generation of ependymal cells [27], as well as in the ageing brain, where neurogenic activity is reduced in concert with the disappearance of ependymal cells [28].…”
Section: Fig 3 Comparison Of the Mouse And Rat Sez (A B)mentioning
confidence: 99%